2017
DOI: 10.1002/2017jg004005
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Stress and Relative Resiliency of Giant Sequoia Groves Experiencing Multiyear Dry Periods in a Warming Climate

Abstract: The relative greenness and wetness of Giant Sequoia (Sequoiadendron giganteum) groves and the surrounding Sierra Nevada, California forests were investigated using patterns in vegetation indices from Landsat imagery for the period 1985–2015. Vegetation greenness (normalized difference vegetation index) and thus forest biomass in groves increased by about 6% over that 30 year period, suggesting a 10% increase in evapotranspiration. No significant change in the surrounding nongrove forest was observed. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…An interesting result of this work is that net evapotranspiration change due to fire in the American River watershed was ∼20% less than that reported by Roche et al (2018). This is the result of (i) using the USGS Tier 1 Collection 1 of Landsat data vs. the precollection data, and (ii) using a normalization that is more representative of the entire vegetation range of California than that of Su et al (2017). While there may be an impact to the annual NDVI average due to variable snow and cloud cover filtering of mid-and high-elevation areas, the improved regression results relative to that used earlier gives us confidence in the current results.…”
Section: Limitations Of Analysismentioning
confidence: 68%
See 2 more Smart Citations
“…An interesting result of this work is that net evapotranspiration change due to fire in the American River watershed was ∼20% less than that reported by Roche et al (2018). This is the result of (i) using the USGS Tier 1 Collection 1 of Landsat data vs. the precollection data, and (ii) using a normalization that is more representative of the entire vegetation range of California than that of Su et al (2017). While there may be an impact to the annual NDVI average due to variable snow and cloud cover filtering of mid-and high-elevation areas, the improved regression results relative to that used earlier gives us confidence in the current results.…”
Section: Limitations Of Analysismentioning
confidence: 68%
“…In a southern Sierra headwater catchment, Oroza et al (2018) found topographic wetness index (TWI) to be an explanatory variable for spatial patterns of soil-water storage only during the dry summer period, after drawdown of soil water following the wet winter and spring periods. Similarly, across a broad area of the southern Sierra, Su et al (2017) found that TWI was not a good predictor of patterns in moisture stress (NDMI) or greenness (NDVI) from Landsat. Using a rich suite of soilmoisture data from headwater catchments in the American and Merced River basins, Saksa et al (2017) modeled catchmentscale water balances, with no significant lateral redistribution.…”
Section: Limitations Of Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Pixels were filtered using the Landsat Collection‐1 Level‐1 Quality‐Assessment Band (CFMask, Foga et al, ) removing all pixels with possible clouds, cloud shadows, or snow contamination. NDVI values were further constrained to a range of 0.2 and 1.0 in order to remove largely unvegetated areas from the analysis (Carlson, Perry, & Schmugge, ). Homogenize Landsat Thematic Mapper (Landsat 5 or LT‐5) and Landsat Operational Land Imager (Landsat 8 or LC8) values to Landsat Enhanced Thematic Mapper values (Landsat 7 or LE‐7) using the following equations (Su et al, , Figure S3): NDVIitalicLandsat5_italichomogenized=NDVIitalicLandsat5×1.13070.0571 NDVIitalicLandsat8_italichomogenized=NDVIitalicLandsat8×0.99380.0167 Temporally interpolate the data. First, smooth the resultant time series using a centred moving average spanning five observation dates.…”
Section: Methodsmentioning
confidence: 99%
“…Over the last century, fire suppression has threatened giant sequoia regeneration by minimizing canopy gaps and exposure of mineral soil, two important factors for germination of this shade intolerant tree (York, Battles, Eschtruth, & Schurr, 2011). Future conditions marked by increased and prolonged drought are expected to put additional stress on giant sequoia (Su et al, 2017). Fortunately, their charisma has deemed them one of the seven natural wonders of the United States (DeFries, 2013), and together, the ecological and cultural importance of the giant sequoia has promoted their current protection by both state and national agencies (Aune, 1994;Leisz, 1994).…”
mentioning
confidence: 99%